(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Presents results of research that had as main objective test the proposed integrated analysis of the distinct Science and Technology outputs (papers and patents) and simultaneously investigate the potential contribution of co-occurrences indicators - co-activity - between different actors in the innovation system of countries organizations and their typologies to better understand the contexts of generation and use of both productions, as well as the dynamic relationship between Science and Technology. It was used as empirical object, the Scientific and Technological Production in the biodiesel field. It was identified 885 published papers and 612 patents. It was found that 80% of the countries that produced patent also produce papers, with strong positive correlation (0.832). A number of organizations that have published papers in the period were 547 and the number of registered patents that was the total of 319. There is co-occurrence in 7% of organizations, which have 25% of total papers and 22% of patents. These co-active organizations are more productive than others (non co-active). With respect to the registration of patents, Companies and Private Research Institutes, co-active registered 7% and Educational Institutes and Public Research Institutes 15%, proving to be more productive. Keywords: Relationship between science and technology. Bibliometrics. Scientometrics. Papers. Patents. Biodiesel. Link para o texto completo (PDF) http://seer.bce.unb.br/index.php/RICI/article/view/10109/7657